Plus ça change? Balkan Archaeology in Search of Identity - Babić, Staša (Ex Novo: Journal of Archaeology, 2024)
Over the last decades, there have been numerous attempts to remedy the perceived delay in the development of archaeology in the Balkans, in the form of conferences, workshops or edited volumes. The frequency seems to testify that the progress is yet to be achieved. Two assumptions are common for these efforts: the archaeological record from the region is rich and highly relevant from the wider European and/or Mediterranean perspective; yet, the discipline itself is permanently petrified in the state of the outdated culture-historical paradigm. This assessment presupposes that the archaeological knowledge has been advancing along a unified trajectory and that at a certain point in time the entire research community operates under the same, universally accepted paradigm. Rather than to partake in the everlasting quest of catching up with the idealized mainstream of the discipline, it may be more productive to consider the ways in which the Balkan archaeology can contribute to the rich multivocality of the discipline, with distinctive experiences of the past and present.